Big Nate : thunka, thunka, thunka - Peirce, Lincoln (Kansas City, Mo. : Andrews McMeel Pub., 2016)
A reprinting of the "Big Nate" comic strip, that follows the adventures of eleven-year-old Nate Wright, a self-proclaimed genius and the all-time record holder for detentions in school history, and his friends and family.
Selections from the "Big Nate" comic strip.
2.9.
3-6.
GN320L
Keywords: Middle school students -- Juvenile fiction; Middle schools -- Juvenile fiction; Behavior -- Juvenile fiction; Schools -- Juvenile fiction; Middle school students -- Comic books, strips, etc -- Fiction; Middle schools -- Comic books, strips, etc -- Fiction; Human behavior -- Comic books, strips, etc -- Fiction; School stories; Humorous stories; Cartoons and comics; Comics (Graphic works); Comic books, strips, etc; Comic books, strips, etc